EXAMINING INTERNAL AUDIT PRACTICES AND CHALLENGES IN INDONESIAN COAL MINING SECTOR - Ghafar, Iyad; Perwitasari, Widya (Widya Mandala Surabaya Catholic University, 2025)
Research Purposes. The research aims to evaluate current internal audit practices, identify challenges faced by auditors, and propose strategies to enhance fraud detection and prevention. Research Methods. The study adopts a qualitative approach, utilizing a case study design to gain an in-depth understanding of internal audit practices at ABC. Data were collected through semi-structured interviews. Thematic analysis was used to identify core themes related to audit practices, challenges, and opportunities for improvement. Research Results and Findings. The study highlights that ABC’s internal audit practices align with global standards, focusing on high-risk areas like procurement. However, limited resources, outdated technology, and data access issues reduce effectiveness. Expanding audit capacity, upgrading technology, enhancing training, and fostering collaboration are essential to improving fraud prevention and governance in the mining sector. This research contributes to enhancing internal audit practices in high-risk industries like mining, providing actionable recommendations to improve fraud prevention and governance frameworks, ensuring more effective and proactive audit processes.